Temporal Changes in Cortical and Hippocampal Expression of Genes Important for Brain Glucose Metabolism Following Controlled Cortical Impact Injury in Mice - Zhou, June; Burns, Mark P.; Huynh, Linda; Villapol, Sonia; Taub, Daniel D.; Saavedra, Juan M.; Blackman, Marc R. (Frontiers in Endocrinology, 2017)
Traumatic brain injury (TBI) causes transient increases and subsequent decreases in brain glucose utilization. The underlying molecular pathways are orchestrated processes and poorly understood. In the current study, we determined temporal changes in cortical and hippocampal expression of genes important for brain glucose/lactate metabolism, and the effect of a known neuroprotective drug Telmisartan on the expression of these genes after experimental TBI. Adult male C57BL/6J mice (n= 6/group) underwent sham or unilateral controlled cortical impact (CCI) injury. Their ipsilateral and contralateral cortex and hippocampus were collected 6 hours, 1, 3, 7, 14, 21, and 28 days after injury. Expressions of several genes important for brain glucose utilization were determined by qRT-PCR. Results: (1) mRNA levels of three key enzymes in glucose metabolism (Hexokinase 1, Pyruvate kinase, and Pyruvate dehydrogenase) were all increased 6 hours after injury in the contralateral cortex, followed by decreases at subsequent times in the ipsilateral cortex and hippocampus; (2) capillary glucose transporter Glut-1 mRNA increased, while neuronal glucose transporter Glut-3 mRNA decreased, at various times in the ipsilateral cortex and hippocampus; (3) astrocyte lactate transporter MCT-1 mRNA increased, whereas neuronal lactate transporter MCT-2 mRNA decreased in the ipsilateral cortex and hippocampus; (4) HK2 (an isoform of Hexokinase) expression increased at all time points in the ipsilateral cortex and hippocampus. GPR81 (Lactate receptor) mRNA increased at various time points in the ipsilateral cortex and hippocampus. These temporal alterations in gene expression corresponded closely to the patterns of impaired brain glucose utilization reported in both TBI patients and experimental TBI rodents. The observed changes in hippocampal gene expression were delayed and prolonged, when compared with those in the cortex. The patterns of alterations were specific to different brain regions and exhibited different recovery periods following TBI. Oral administration of Telmisartan (1mg/kg, for 7 days, n=10 per group) ameliorated cortical or hippocampal mRNA for Glut-1/3, MCT-1/2 and Pyruvate dehydrogenase in CCI mice. These data provide molecular evidence for dynamic alteration of multiple critical factors in brain glucose metabolism post TBI, and can inform further research for treating brain metabolic disorders post TBI.